# Calculator search results

Formula
Solve the equation
Graph
$4 - \left ( 3 x - \left ( 5 x - y \right ) + 1 \right ) = 3$
$x$Intercept
$\left ( 0 , 0 \right )$
$y$Intercept
$\left ( 0 , 0 \right )$
$4- \{ 3x- \left( 5x-y \right) +1 \} = 3$
$x = \dfrac { 1 } { 2 } y$
 Solve a solution to $x$
$4 - \left ( 3 x \color{#FF6800}{ - } \left ( \color{#FF6800}{ 5 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ y } \right ) + 1 \right ) = 3$
 Change the symbol of each term in parentheses when there is a (-) symbol in front of parentheses 
$4 - \left ( 3 x \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } + \color{#FF6800}{ y } + 1 \right ) = 3$
$4 - \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } + y + 1 \right ) = 3$
 Calculate between similar terms 
$4 - \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } + y + 1 \right ) = 3$
$4 \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) = 3$
 Change the symbol of each term in parentheses when there is a (-) symbol in front of parentheses 
$4 + \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 1 } = 3$
$\color{#FF6800}{ 4 } + 2 x - y \color{#FF6800}{ - } \color{#FF6800}{ 1 } = 3$
 Subtract $1$ from $4$
$\color{#FF6800}{ 3 } + 2 x - y = 3$
$\color{#FF6800}{ 3 } + 2 x \color{#FF6800}{ - } \color{#FF6800}{ y } = 3$
 Move the rest of the expression except $x$ term to the right side and replace the sign 
$2 x = y$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ y }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ y } \color{#FF6800}{ \div } \color{#FF6800}{ 2 }$
$x = y \color{#FF6800}{ \div } \color{#FF6800}{ 2 }$
 Convert division to multiplication 
$x = y \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
$x = \color{#FF6800}{ y } \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
 Simplify the expression 
$x = \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ y }$
$y = 2 x$
 Solve a solution to $y$
$4 - \left ( 3 x \color{#FF6800}{ - } \left ( \color{#FF6800}{ 5 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ y } \right ) + 1 \right ) = 3$
 Change the symbol of each term in parentheses when there is a (-) symbol in front of parentheses 
$4 - \left ( 3 x \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } + \color{#FF6800}{ y } + 1 \right ) = 3$
$4 - \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } + y + 1 \right ) = 3$
 Calculate between similar terms 
$4 - \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } + y + 1 \right ) = 3$
$4 \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) = 3$
 Change the symbol of each term in parentheses when there is a (-) symbol in front of parentheses 
$4 + \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 1 } = 3$
$\color{#FF6800}{ 4 } + 2 x - y \color{#FF6800}{ - } \color{#FF6800}{ 1 } = 3$
 Subtract $1$ from $4$
$\color{#FF6800}{ 3 } + 2 x - y = 3$
$\color{#FF6800}{ 3 } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } - y = 3$
 Move the rest of the expression except $y$ term to the right side and replace the sign 
$- y = - \left ( 2 x \right )$
$- y = \color{#FF6800}{ - } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \right )$
 Organize the expression 
$- y = \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x }$
$\color{#FF6800}{ - } \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x }$
 Change the sign of both sides of the equation 
$y = 2 x$
 그래프 보기 
Graph
Solution search results